OCULAR ROSACEA – BLEPHARITIS UNCOMMON IN CHILDREN - Filho, Fred Bernardes; Santos, Maria Victória Pinto Quaresma; de Carvalho, Felipe Nazareth de Matos Pinto; de Castro, Carlos Gustavo Carneiro; Fernandez, Natália Monteiro; Rocha, Ana Rita; Timbó, Renata Pinto Fernandes; Sulzer, Denise (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Rosacea is a disease of unknown etiology which affects both the skin and the eye. There is high rate of ocular manifestations in patients with rosacea, whose signs and symptoms are related to the dysfunction of Meibomius glands. We report a case of a male child with unilateral blepharitis. Due to the injury is recurrent, childhood-onset, the patient had normal laboratory tests and in the absence of central facial lesions, biopsy was required for diagnosis. His- topathological examination revealed acanthosis, dilated capillaries and venules in the papillary and reticular dermis, perivascular and interstitial lymphocytic infiltrate. This case illustrates a subtle finding that rosacea can be extremely important for early diagnosis and monitoring. KEYWORDS – Rosacea; Eyelid diseases; Meibomian glands; Blepharitis; Child.